2016
DOI: 10.3892/or.2016.4713
|View full text |Cite
|
Sign up to set email alerts
|

miR-491-5p suppresses cell growth and invasion by targeting Notch3 in nasopharyngeal carcinoma

Abstract: MicroRNAs (miRNAs) have critical roles in the progression of nasopharyngeal carcinoma (NPC), a highly invasive and metastatic cancer that is widely prevalent in Southern China. miR-491-5p has been implicated in multiple types of cancer; however, its biological role and underlying mechanism in NPC have not been fully explored. In the present study, we found that miR-491-5p was downregulated in NPC tissues and cell lines compared with the corresponding normal counterparts. Overexpression of miR-491-5p significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 31 publications
(35 reference statements)
0
21
0
Order By: Relevance
“…Low expression of miR‐491‐5p has been reported in glioblastoma and oral squamous cell carcinoma . In NPC, we found that miR‐491‐5p was downregulated in NPC tissues compared with normal tissues and that miR‐491‐5p suppresses cell growth and invasion by targeting Notch3 . We therefore predicted that over‐expression of XIST was associated with dysregulation of Notch3 in NPC.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Low expression of miR‐491‐5p has been reported in glioblastoma and oral squamous cell carcinoma . In NPC, we found that miR‐491‐5p was downregulated in NPC tissues compared with normal tissues and that miR‐491‐5p suppresses cell growth and invasion by targeting Notch3 . We therefore predicted that over‐expression of XIST was associated with dysregulation of Notch3 in NPC.…”
Section: Discussionmentioning
confidence: 72%
“…These results indicate that miR‐491‐5p suppresses XIST function. We previously reported that miR‐491‐5p suppresses Notch3 expression by directly targeting the 3′ untranslated region of Notch3 mRNA . Thus, XIST may regulate miR‐491‐5p to modulate Notch3 in NPC cells.…”
Section: Resultsmentioning
confidence: 99%
“…What's more, miR‐491 targets G‐protein‐coupled receptor kinase‐interacting protein 1 (GIT‐1), which blocked the activation of NF‐κB to attenuate cancer stem cell‐like properties of hepatocellular carcinoma . Besides, miR‐491 can also regulate its target genes, such as IGF2BP1, CTGF, TPX and Notch, functioning as tumour suppressor. Our study showed miR‐491‐5p suppressed the proliferation of human osteosarcoma cells and increased the cell apoptosis in vitro by targeting FOXP4 .…”
Section: Discussionmentioning
confidence: 99%
“…4 Among these miRNAs, miR-491-5p, located in the fourth intron of focadhesin (FOCAD) has been reported to be deregulated in several human cancers. 5, 6, 7, 8, 9 miR-491-5p acts as a tumor suppressor by targeting JMJD2B in ERa-positive breast cancer. 10 miR-491-5p and its targeted gene GIT1 are considered biomarkers for the prognosis of oral squamous cell carcinoma.…”
mentioning
confidence: 99%